Magnetic resonance brain imaging in people with dizziness: a comparison with non-dizzy people. Issue 5 (1st May 2002) - Colledge, N; Lewis, S; Mead, G; Sellar, R; Wardlaw, J; Wilson, J
Abstract : Background: Dizziness is a common symptom affecting about 30% of people over the age of 65. Objective: To investigate the hypothesis that structural abnormalities of the brain and cervical cord are more common in dizzy than in non-dizzy subjects. Methods: A case–control study of subjects over the age of 65 with and without dizziness: 125 dizzy subjects and 86 non-dizzy subjects were recruited from the community through articles in the local press. Magnetic resonance imaging (MRI) of the brain and neck was performed, and was read by a consultant neuroradiologist blind to the clinical details. Results: All dizzy subjects and all controls had at least one structural abnormality. Cerebral atrophy was found in 86% of dizzy subjects and 85% controls (p = 1.0) At least one white matter lesion was found in 69% of dizzy subjects and 78% controls (p = 0.21). White matter lesions in the midbrain were more common in dizzy than in non-dizzy subjects (22% v 4%, p < 0.001). There were no significant differences in the prevalence of cord compression, cervical subluxation, facet joint degeneration, vertebral artery compression, or vertebral artery occlusion between dizzy and non-dizzy subjects. Conclusions: Structural abnormalities of the brain and neck are common in both dizzy and non-dizzy subjects. "Routine" MRI is unlikely to reveal a specific cause for dizziness. The observation of more frequent white matter lesions in the midbrain in dizzy subjects requires further study to determine whether small vessel changes could cause dizziness in older people.